Poly (3,4-ethylene dioxythiophene)/copper sulfide hybrid thermoelectric materials with large Seebeck coefficient around room temperature - Ahmed, N. S.; Karaman, F. (NATL INST OPTOELECTRONICS, 2018)
Nanocomposites were prepared from poly (3,4-ethylene dioxythiophene): poly (styrene sulfonic acid) (PEDOT:PSSA) / copper sulfide synthesized in this study. Seebeck coefficient and electrical conductivity of PEDOT: PSSA were measured as 1125 mu V/K and 1.08 S/cm, respectively. Electrical conductivities of the nanocomposites do not decrease considerably whereas their Seebeck coefficients were found 4 or 6 times larger than pristine polymer. Their power factors were found 15 or 19 times higher than pristine polymer. The largest Seebeck coefficient was measured as 7000 mu V/K and the highest power factor was found as 2646 mu W/mK(2). These are the highest values reported up to date for polymer based thermoelectric materials.
Keywords: Thermoelectric; Poly (3,4-ethylene dioxythiophene); Copper sulfide; Seebeck coefficient; Nanocomposite; COMPOSITE FILMS; PEDOT; PERFORMANCE; Materials Science; Optics; Physics